Accelerated Hydrogen Evolution Kinetics on NiFe‐Layered Double Hydroxide Electrocatalysts by Tailoring Water Dissociation Active Sites. Issue 10 (19th January 2018) - Chen, Guangbo; Wang, Tao; Zhang, Jian; Liu, Pan; Sun, Hanjun; Zhuang, Xiaodong; Chen, Mingwei; Feng, Xinliang
Abstract: Owing to its earth abundance, low kinetic overpotential, and superior stability, NiFe‐layered double hydroxide (NiFe‐LDH) has emerged as a promising electrocatalyst for catalyzing water splitting, especially oxygen evolution reaction (OER), in alkaline solutions. Unfortunately, as a result of extremely sluggish water dissociation kinetics (Volmer step), hydrogen evolution reaction (HER) activity of the NiFe‐LDH is rather poor in alkaline environment. Here a novel strategy is demonstrated for substantially accelerating the hydrogen evolution kinetics of the NiFe‐LDH by partially substituting Fe atoms with Ru. In a 1 m KOH solution, the as‐synthesized Ru‐doped NiFe‐LDH nanosheets (NiFeRu‐LDH) exhibit excellent HER performance with an overpotential of 29 mV at 10 mA cm −2, which is much lower than those of noble metal Pt/C and reported electrocatalysts. Both experimental and theoretical results reveal that the introduction of Ru atoms into NiFe‐LDH can efficiently reduce energy barrier of the Volmer step, eventually accelerating its HER kinetics. Benefitting from its outstanding HER activity and remained excellent OER activity, the NiFeRu‐LDH steadily drives an alkaline electrolyzer with a current density of 10 mA cm −2 at a cell voltage of 1.52 V, which is much lower than the values for Pt/C–Ir/C couple and state‐of‐the‐art overall water‐splitting electrocatalysts. Abstract : The sluggish hydrogen evolution reaction (HER) kinetics on a NiFe layered double hydroxide (LDH) are substantially sped up in a novel approach by tailoring its water dissociation active sites in alkaline solutions. The resultant Ru‐doped NiFe‐LDH nanosheet exhibits a greatly enhanced HER activity in alkaline solution, which is superior to those of Pt/C and state‐of‐the‐art Pt‐free electrocatalysts.